2021
DOI: 10.1055/s-0040-1722625
|View full text |Cite
|
Sign up to set email alerts
|

Tibial Cut Accuracy in Mechanically Aligned Total Knee Arthroplasty Using Extensor Hallucis Longus Tendon to Determine Extramedullary Tibial Guide Position

Abstract: This study aimed to determine the tibial cut (TC) accuracy using extensor hallucis longus (EHL) tendon as an anatomical landmark to position the total knee arthroplasty (TKA) extramedullary tibial guide (EMTG), and its impact on the TKA mechanical alignment (MA). We retrospectively studied 96 TKA, performed by a single surgeon, using a femoral tailored intramedullary guide technique. Seventeen were prior to the use of the EHL and 79 used the EHL tendon to position the EMTG. We analyzed preoperative and postope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
1
1
Order By: Relevance
“…Other authors who analyzed the percentage of malaligned cases and the mean alignment deficit [ 27 ] found navigation to be associated with slightly better results. The mean TCA obtained in our series following navigation was 87.65°, not too different from the values reported by some authors [ 28 , 29 ] and very far from the 96% reported in others [ 30 ]. Similarly, we found no correlation between the value of the TCA and the presence or absence of a previous deformity.…”
Section: Discussioncontrasting
confidence: 89%
“…Other authors who analyzed the percentage of malaligned cases and the mean alignment deficit [ 27 ] found navigation to be associated with slightly better results. The mean TCA obtained in our series following navigation was 87.65°, not too different from the values reported by some authors [ 28 , 29 ] and very far from the 96% reported in others [ 30 ]. Similarly, we found no correlation between the value of the TCA and the presence or absence of a previous deformity.…”
Section: Discussioncontrasting
confidence: 89%
“…3,4 Although some reports suggest that the intramedullary guide has a higher accuracy, [5][6][7] Phillips et al 8 reported that 76% of surgeons prefer the extramedullary guide. When using an extramedullary technique on the tibial side, the intercondylar eminence, 9,10 medial border of the tibial tubercle, 11 extensor hallucis longus, 12,13 second metatarsal bone axis, 14 and the line connecting the medial and lateral malleolus of the ankle 5,6 have been used as references, but no clear criteria have been established. The usefulness of computer-assisted measurements 15,16 and robotic systems 17,18 has also been reported, but they are not widely used because of cost issues.…”
Section: Introductionmentioning
confidence: 99%